Pemanfaatan Fly Ash sebagai Filler Campuran Reclaimed Asphalt Pavement (RAP) pada Pembuatan Daur Ulang Asphalt Concrete – Wearing Course (AC-WC) - Sulaiman, Sulaiman; Kurniati, Kurniati; Zhuha, Farah (Jurnal Teknologi, 2025)
Reclaimed Asphalt Pavement is a waste from dredging pavement that has been damaged due to the expiration of its planned life or excessive traffic loads. The demolition material comes from Medan - Banda Aceh road, Besitang, North Sumatra, demolished using Cold Milling Machine. Research was conducted to handle Reclaimed Asphalt Pavement using the recycling method. The research used Reclaimed Asphalt Pavement by adding fly ash as filler to determine the mixture characteristics and Marshall parameter values as recycled Asphalt Concrete - Wearing Course mixture. The research method follows the general standard specifications applicable to Asphalt Concrete - Wearing Course. The extraction results obtained the asphalt content in Reclaimed Asphalt Pavement of 4.75% with aggregate gradation according to specifications. The Optimum Asphalt Content used was 5.9. The total weight of filler is 7.87%, fly ash as a substitute material for filler with a percentage of fly ash addition of 0%, 4%, 6%, 7% and 8% of the total weight of filler. In the 0%, 4%, 6%, 7% and 8% fly ash mixture, the values of stability, flow, Marshall Quotient, Void In Mineral Aggregate, and Void Filled with Bitumen meet the required specifications. While the Void In Mix value is greater than required.